(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
Analysis of the supervisory function based on 2017 data questions the problem that the implementation of the supervisory function has so far not been carried out effectively, the reason being that the implementation of government performance audits so far has not been in accordance with what was planned, as stated in the Inspectorate’s government agency performance report (LAKIP) book. Makassar City Region in 2017 stated that the implementation of standard operating procedures (SOP) within the scope of the Makassar City Regional Inspectorate was not yet optimal, there was a limited number of human resources compared to the size of the supervision object, limited budget allocation in the field of supervision and so on. For the sake of reviewing, an in-depth study was carried out starting from Preliminary Supervision, Concurrent (While work is in progress) and Feedback Supervision. Research data collection uses qualitative research methods. From the use of qualitative methods, the researcher obtained results from the problem behind this research, namely an increase in the quality of supervision performance of the Makassar City.